Drama Gong sebagai Media Pendidikan dan Kritik Sosial - I Wayan Sugita (Pusat Kajian Bali Universitas Udayana, 2020)
This article is aimed at finding out the positive politeness strategies used in utterances by characters in Little Women movie. The data were retrieved from Little Women movie directed by Hedwig (2019). This article applied documentation method in collecting the data and used qualitative method in analyzing the data. The collected data were analyzed in terms of the positive politeness strategies applied in it. The theories used to analyze were the theory of positive politeness strategy proposed by Brown and Levinson (1987). The findings of the article showed that there were 29 data of positive politeness strategy found in Little Women movie. The data found consist of eleven types of positive politeness strategies, namely exaggerate, intensify interest to hearer in the speaker’s contribution, use in-group identity markers, seek agreement, avoid disagreement, joke, offer and promise, be optimistic, include both speaker and hearer in the activity, give or ask for reasons, assume or assert reciprocity, and give gifts.